EFEKTIVITAS SOAL-SOAL MATEMATIKA TIPE PISA MENGGUNAKAN KONTEKS BUDAYA SUMATERA UTARA UNTUK MENDESKRIPSIKAN KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIS SISWA SMP KOTA MEDAN - Hafni Hasanah (AXIOM : Jurnal Pendidikan dan Matematika, 2017)
This study aims to explain the efectiveness of mathematical problem type of PISA using cultural context of North Sumatera to describe reasoning dan komunication mathematic ability.This type of research is development research type development study.  The development model used is a model Plomp. The questions fill efective criteria that is obtained through the response of teacher and student. The teacher and student like and feeling interested in the question, the questions can be used to measure the student ability in mathematic reasoning and communication, the students are feeling motivated to answer the questions. The result research got from mean of result reasoning ability mathematic of student from school,high (26.00),middle (25.85), and low (14.04). The result of mean test from mathematic communication ability of student from school, high (26.15), middle (22.80), and low (24.35). Finding of the research shows that the higher the level of the questions, the lower score that student get.